Retrospective Analysis of Heartworm (Dirofilia immitis) Prevention Medication Compliance and Economic Value in Dogs in Veterinary Practices in Australia - Mwacalimba, Kennedy; Wright, Andrea; Giannakakis, Konstantinos; L'Estrange, Richard; Nguyen, Tinh-Son (Frontiers in Veterinary Science, 2021)
Abstract Background: Canine heartworm (HW) is endemic in Australia. Prevention usually involves monthly topical or oral preventives, or annual injections of extended-release moxidectin (ProHeart SR-12*), hereafter referred to as injectable moxidectin (IM). Poor compliance can leave dogs susceptible to infection. This Pharmacoeconomics study used retrospective transactional data from 52 Australian veterinary practices to examine the economic value of compliance, revenue and patient retention associated with veterinarian-sourced canine HW prevention. Methods: This longitudinal descriptive study utilized anonymized transaction records of 228,185 dogs identified to have visited a veterinary practice at least twice in the period 2010–2015. Purchase compliance against a benchmark of 12 months HW protection per year was measured for IM or monthly HW (MHW) preparations each year and for consecutive years. The average annual cost per dog by preventative modality was also determined. Results: Between 2010–2015, of the 228,185 dogs identified, 73.0% recorded either zero or one purchase of HW preventive from their veterinary clinic; 18.7% recorded at least two IM purchases and 10.6% purchased MHW prevention at least twice. Single year purchase compliance was 92.8–96.9% for IM versus 26.9–36.5% for dogs receiving MHW products. Consecutive year purchase compliance was 76.7% for IM and 24.4% for MHW medications. Dog owners spent $AU108.29/dog/year (Australian dollars) on IM versus $AU131.96/dog/year on MHW prevention products which may have treated other parasites concurrently, although repeat MHW purchasers only purchased enough to cover an average of 7.2 months per year. Dogs recording at least two HW prevention transactions generated more revenue for veterinary practices/dog/year compared to dogs with less than two. Finally, dogs receiving IM, especially those started at <15 months old, had the highest retention rate in this population. Conclusions: In the 5 years from 2010–2015, 73% of dog owners who visited a veterinary practice at least twice made less than two purchases of HW preventatives from the veterinary practice. For those with at least two preventative purchases, 76.7% of dogs receiving IM and 24.4% of dogs prescribed MHW products purchased enough doses to provide continuous protection over the observation period. *known as ProHeart®12 in the US